Acute exposure to an electric field induces changes in human plasma 9-HODE, 13-HODE, and immunoreactive substance P levels: Insight into the molecular mechanisms of electric field therapy. Issue 2 (2016) - Nakagawa-Yagi, Yuzo; Hara, Hiroyuki; Nakagawa, Fumiyuki; Sato, Masashi; Hara, Akikuni
No abstract available